Soil erosion and sediment transport research in tropical Africa - Lal, R. (1985)
This paper reviews the magnitude of soil erosion in tropical Africa and relates it to erodibility, erosivity and landform in different ecological regions There are few direct measurements of erosivity and erodibility in tropical Africa and the relevance of using the Universal Soil Loss Equation in estimating these parameters is reviewed. Soil erodibility is not a fixed parameter and changes with time. Although localized rates of soil erosion can be high, the erosion rates derived from sediment loads in rivers are often low. Most of the available data on sediment loads of African rivers are 10–20 years old, and little research information is available on the delivery ratios associated with different catchments. Rapidly changing land use is one of the major factors responsible for accelerated soil erosion, and the effects of deforestation, grazing, fire, and of cultural practices are discussed. The economics of soil erosion is reviewed in terms of loss in productivity and siltation of reservoirs. Research and development needs are listed.